Interpretation of ICJ in Nuclear Weapon Disarmament: Marshall Island v. the United Kingdom - Yordan Gunawan; Fatra Alamsyah; Elvita Anggoro Wati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2022)
In 2014, the Republic of the Marshall Islands (RMI) filed lawsuits against several major Nuclear Weapons States (NWS) to the International Court of Justice (ICJ). In connection with the conclusion of the nuclear arms race and disarmament, RMI filed a lawsuit alleging a breach of negotiating duties. However, the ICJ concluded that such a complaint should be dismissed since there was no urgency in the case. There is a concern that this judgment does not follow the pattern and practice of the ICJ’s rulings. Some scholars conclude that there is a potential of power or political link in the ICJ judgment that cannot be explained by law. The United Kingdom has nuclear weapons and dominates the nuclear arms race. The purpose of this study is to examine the hegemony NWS, which leads the ICJ to reject the Marshal Islands case in the context of negotiating duties related to the cessation of the race and nuclear disarmament. The research method applied in this study is a normative legal research method. Secondary data derived from the statutory approach, analytical approach, legal conceptual approach, and factual approach were used in the study. The result of the study showed that the ICJ has jurisdiction over the case to give advisory opinions and to settle this case in order to give additional provision in Article VI of The Non-Proliferation Treaty of 1968 (NPT).